Central bank policy rates: Are they cointegrated? - Guglielmo Maria Caporale; Hector Carcel; Luis A. Gil-Ala\~na (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper analyses the stochastic properties of and the bilateral linkages between the central bank policy rates of the US, the Eurozone, Australia, Canada, Japan and the UK using fractional integration and cointegration techniques respectively. The univariate analysis suggests a high degree of persistence in all cases: the fractional integration parameter d is estimated to be above 1, ranging from 1.26 (US) to 1.48 (UK), with the single exception of Japan, for which the unit root null cannot be rejected. Concerning the bivariate results, Australian interest rates are found to be cointegrated with the Eurozone and UK ones, Canadian rates with the UK and US ones, and Japanese rates with the UK ones. The increasing degree of integration of international financial markets and the coordinated monetary policy responses following the global financial crisis might both account for such linkages.
Keywords: C22; C32; E47; 330; interest rates; long memory; fractional integration and cointegration